please solve this problem with explanation
Attachments:
![](https://hi-static.z-dn.net/files/d41/c3d42da7bc0db17f48f075a97f336ffd.jpg)
Answers
Answered by
1
Answer:
Just equate the coefficients,
Step-by-step explanation:
2x+y=10(given)
y=10-2x ......(i)
x-y=-1 (given)
put the value of y from(i)
x-(10-2x)=-1
x-10+2x+1=0
3x=-11
x=-11/3
So y=10-2x=10-2(-11/3)=10+22/3=52/3
x-z=2 (given)
-11/3-z=2
z=-11/3-2
z=-17/3
Pls check the calculations .I did them in rush.
Answered by
1
Step-by-step explanation:
hope this helps you friend
Attachments:
![](https://hi-static.z-dn.net/files/d85/b4e805e245f70560f8db390fc1e486b3.jpg)
Similar questions